The Critical Discourse Analysis of Translation Shift in إسرائيل /Israel/ in Republika - Nur Aisiyah Fadhilah; Apipudin Apipudin (Proceedings of AICS - Social Sciences, 2018)
This research studies the translation shift in the word ‘Israel’. Word ‘Israel’ initially referred to the Prophet Ya’qub, but in the present, the meaning has shifted to the state of Israel in the association with colonizer and Zionist. This study aims to analyze chronological history of the shifting meaning of the word Israel and the discourse that was built in it. This research uses qualitative method with descriptive approach. The data contained in this research is sourced from mass media of Republika online was entitled